Incest and the literary imagination - Barnes, Elizabeth, 1959- (University Press of Florida, 2002)
''Its range--both chronological and methodological--as well as the consistently high quality of its essays makes this collection stand out. A timely and important collection ... on literary representations of incest [that will] become the touchstone for further work in the field.